Employing a Force and Motion Learning Progression to Investigate the Relationship between Task Characteristics and Students’ Conceptions at Different Levels of Sophistication - Just, Anna Monika; Vorholzer, Andreas; von Aufschnaiter, Claudia; Justus Liebig University Giessen (My University, 2023)
Research has demonstrated that when learning mechanics, students’ conceptions (SCs) improve gradually (1) and are often activated depending on problem features (2). The aim of this study is to combine these two research lines to investigate how different task characteristics affect the activation of SCs at different levels of sophistication. Data were collected from N = 356 students using a paper–pencil test in which conceptual and contextual task characteristics (CCTCs) are varied systematically across ordered multiple-choice items. Answer options were constructed according to the four levels of a force and motion learning progression. Results, obtained using quantitative methods (e.g., Rasch analysis and regression), demonstrate that the effects of CCTCs may differ at different levels of SCs. For the direction of problem, for example, activating the correct conception, assuming force proportional to acceleration, seems to be easier in tasks asking for the resulting motion. However, activating more appropriate conceptions regarding lower levels, e.g., assuming force proportional to velocity, compared to a rather undifferentiated understanding of force and motion, seems to be easier in tasks asking for the forces. Results of our study can be used for choosing tasks with specific CCTCs to support conceptual change along specific steps of a learning path.
Keywords: conceptual change; context; learning progression; Newtonian mechanics; ordered multiple-choice; students’ conceptions; task characteristics; ddc:530